POTENSI PENERAPAN PRODUKSI BERSIH DI PENGOLAHAN SUSU PASTERURISASI SISTEM KEJUT LISTRIK - Adam Virgi; Eko Aprilianto; Muhammad Nur kholis (Agroindustrial Technology Journal, 2018)
E-milk is one of the products produced by TIP CORP, a study group engaged in the field of entrepreneurship. The application of clean production in the industry has a positive influence on the companies that implement it, both financially and non-financially. The number of milk spills in the packaging process makes the results less than the maximum so that it is necessary to apply the potential of clean production with the calculation of the net production feasibility analysis, from the calculation of the pay back period of the purchase of a liquid filling machine is 3.8 months. Potential implementation of cleaner production needs to be done because it can help prevent and reduce environmental impacts through the product life cycle.